Organic carbon facilitates the release of organic phosphorus by converting stable organic phosphorus into bioavailable forms in eutrophic sediments - Wang, Yan; Chen, Xiang; Li, Cai; Kong, Ming; Tian, Yan; Wang, Xia; Ji, Ying; Zhang, Lan; Hang, Xiaoshuai (Journal of environmental sciences (China), 2025)
•Humic and Fulvic acid fractions of organic matter accelerate the release of organic phosphorous.•Degradation and mineralization of organic carbon increase the mineralization rate of organic phosphorous. Organic phosphorus (OP) constitutes an important fraction of total phosphorus in lake sediments, with its mobility being influenced by mineralization and transformation of organic carbon (OC). OP and OC co-exist in various forms in the environment, thus a thorough investigation on the impact of OC fractions on the release of OP in sediments should be comprehensively carried out. This study determined the chemical forms of OP and OC in the sediments over four seasons in Lake Taihu and found temporal and spatial variations in their concentrations. The concentration of total OP and total OC ranged from 133 to 348 mg/kg and 4.77 to 21.19 mg/kg, respectively. Correlation between chemical fractions of OP and OC also revealed that NaOH-extracted OP, and fulvic acid-bound and humic acid-bound OP were positively correlated with humic-OC and hot hydrolysis-OC. These results suggest that the algal-derived OC degradation and mineralization may enhance OP mineralization, converting stable or moderately active OP into active forms or inorganic phosphorus under cyanobacterial bloom. This study provides insight and guiding support for investigating the impact of organic matter components on the transformation of OP after cyanobacterial degradation in eutrophic lakes. [Display omitted]